PENGUKURAN KINERJA BERBASIS BALANCED SCORECARD PADA KOPERASI PEGAWAI PT. TELKOM (KOPEGTEL) INSAN DENPASAR - Satriyadi, I Gede Hardiaksa (E-Jurnal Akuntansi, 2015)
This study aimed to determine the measurement of performance based on the Balanced Scorecard of Koperasi Pegawai PT. Telkom (KOPEGTEL) Insan Denpasar. The performance measurementis done to suppress the improper behavior and stimulate the behavior that benefits the organization through feedback on performance and rewards. The perspective balancedscorecard used are financial, customer, internal business process, and learning and growth. The data analysis technique used the descriptive analysis to describe the state of data in general. Based on the analysis, we found that the measurement of the performance of the financial perspective showed that the ROE in 2012 by 12% and 2013 by 20%. The Business profits (SHU) for each member in 2013 was amounted to Rp 791.430,59 which has increased Rp 344.994,58 compared with 2012. The average of customer satisfaction is -0.10553 and showed that customers are very satisfied with the quality and services rendered. The average of employee satisfaction is at -0.0856 which indicated employees feel very satisfied with the quality which are provided and showed by the productivity of employees which is remained at 14.83%.
Keywords: Balanced Scorecard, Penilaian Kinerja, Koperasi